Potential of cowpea variety mixtures to increase yield stability in subsistence agriculture: preliminary results - Okonya, J.; Maass, Brigitte L. (Hindawi Limited, 2014)
Cowpea Vigna unguiculata (L.) Walp. is an important leafy vegetable and grain legume in Uganda. Unlike in commercial agriculture, where variety mixtures are known to give higher and more stable yields, the performance of cowpea variety mixtures in subsistence agriculture is little known. Mixtures containing up to four cowpea varieties were subjected to all possible 2-way, 3-way, and 4-way combinations. These cowpea varieties and mixtures were grown at three locations in Soroti and Kumi districts in order to assess the relative mixture effect, defined as: Mixture effect (%) = (mixture yield − pure line component average)/pure line component average × 100. Yield data was subjected to one-way ANOVA using the GLM procedure of SYSTAT. PLABSTAT was used to generate ecovalence () values as a measure of stability with low ecovalence values indicating higher stability. The total cowpea dry matter (DM) yield was in the range of 3.7–6.7 g/m2 (leaf) and 12.1–36.7 g/m2 (grain), respectively. Mixture effects were between −9.3–14.0% (leaf) and −30.3–21.9% (grain). Yield stability spanned = 0.06–5.30 (leaf) and = 4.45–894.84 (grain). The results suggested that yields of cowpea variety mixtures grown in marginal environments were more stable than of single varieties but not all mixtures yielded more than single varieties.